Islam dalam hegemoni Majapahit: Interaksi Majapahit dengan Islam abad ke-13 sampai 15 Masehi - Isna Roikhatul Janah; Lutfiah Ayundasari (Universitas Negeri Malang, 2021)
Islam has existed in Indonesia since the time of traditional kingdoms, and the emergence of Islam on the Java island and growing very rapidly occurred at the end of the Hindu Buddhist era, exactly the Majapahit era. We can see the proof of this with the discovery of the ancient Troloyo Islamic Tomb complex in Mojokerto, which is close to the location of the capital city of Majapahit.. The freedom in Majapahit government system caused Islamization well progressed and increased the moslem population, even more in the coast. This cannot be separated from the services of the preachers, especially Syekh Jumadil Kubro and Maulana Malik Ibrahim. Furthermore, one of the queen was a princess came from Campa. Then born a prince from a chineses queen in Majapahit, and he came back to Majapahit to take his throne and change Majapahit to Islamic kingdom by build a kingdom named Kesultanan Demak. Islam sudah ada di Indonesia sejak zaman kerajaan tradisional, dan munculnya Islam di Pulau Jawa serta berkembang sangat pesat terjadi saat akhir zaman Hindu Buddha yaitu zaman Majapahit. Buktinya dapat kita lihat dengan penemuan kompleks Makam Islam kuno Troloyo di Mojokerto, berdekatan dengan lokasi ibukota Majapahit. Bebasnya sistem pemerintahan di Majapahit menyebabkan Islamisasi berjalan lancar dan masyarakat muslim terus bertambah, terutama di daerah pesisir. Ini tidak lepas dari jasa para pendakwah, terutama Syekh Jumadil Kubro dan Maulana Malik Ibrahim. Selain itu juga istri salah satu raja Majapahit adalah seorang putri dari Negeri Campa. Kemudian lahir Raden Patah dari seorang istri raja yang merupakan seorang Putri Cina, dan ia kembali ke Majapahit demi menuntut takhta dan mengubah Majapahit menjadi kerajaan Islam dengan mendirikan Kesultanan Demak.